Extreme High Yield of Tropical Rice Grown Without Fertilizer on Acid Sulfate Soil in South Kalimantan, Indonesia - Erry Purnomo; Yasuyuki Hashidoko; Toshihiro Hasegawa; Mitsuru Osaki (UNIVERSITY OF LAMPUNG, 2010)
Extreme High Yield of Tropical Rice Grown Without Fertilizer on Acid Sulfate Soil in South Kalimantan, Indonesia (E Purnomo, Y Hashidoko, T Hasegawa and M Osaki): Local rice arieties are commonly grown by the farmers located in acid sulfate soil area of South Kalimantan. In South Kalimantan, more than 100 local rice varieties can be found. In 1999, a farmer found one hill (with 5 tillers) rice plant near a canal, later called Padi Panjang. The rice had panicle length of 50 cm. The panicle length of common local rice varieties are 25 cm. Since the finding, the farmer multiplied the seed for 3 years to get a reasonable amount of seeds for nearby farmers to use. In 2004, there were 25 farmers grow the Padi Panjang by themselves. Their paddocks are widely spread out in Aluh-Aluh and Gambut districts. We take this opportunity to investigate yield variation of the Padi Panjang that may be affected by soil properties variability. Ten paddocks out of the 25 paddock were selected. At harvest time (in July-August), we measured the rice yield and collected soil sample from the 10 paddocks. We found that the soil condition in the selected paddocks were marginally suitable for growing improved rice. Without fertilizer, however, the rice yield varied from 3.21 to 8.09 Mg ha-1. We also observed that the rice yield variations associated with tillers number. We did not find any correlation between rice yields with some selected soil properties, except it was observed that the tillers number was negatively correlated with soil electrical conductivity (EC). The extreme yield of Padi Panjang might be explained the involvement of N fixing bacteria and P solubilizing bacteria, large rooting system and the ability of Padi Panjang root in modifying the rhizosphere soil.